Novel Insights in Systemic Lupus Erythematosus and Atherosclerosis - Teixeira, Vítor; Tam, Lai-Shan (Frontiers in Medicine, 2018)
Introduction The systemic inflammatory nature of systemic lupus erythematosus (SLE) is well patent not only in the diverse clinical manifestations of the disease but also in the increased risk of premature atherosclerosis and cardiovascular events (CVE), making SLE one of the most complex diseases to study and manage in clinical practice. Aim To travel from old aspects to modern insights on the physiopathology, new molecular biomarkers, imaging methods of atherosclerosis assessment, and the potential treatments of atherosclerosis in SLE. Methods We conducted a literature search using PubMed database and performed a critical review. Conclusion/discussion Several developments have taken place in the understanding of the relationship between SLE and premature atherosclerosis. Nevertheless, cardiovascular diseases are still the major cause of reduced life expectancy in SLE and the main cause of death. The lack of standardization methods for the imaging assessment of atherosclerosis in SLE and the multifactorial nature of the disease are well patriated in the difficulty of achieving consistent and reproducible results among studies that focus in cardiovascular risk assessment and prediction. A raising number of molecular biomarkers of atherosclerosis have been proposed, but the combination of several biomarkers and risk factors may better estimate cardiovascular disease risk. Moreover, the development of effective therapies to prevent progression of atherosclerosis and CVE shall address systemic inflammation.